THE BEGINNING OF THE 1916 UPRISING IN SOUTHERN KYRGYZSTAN AND ITS LEADERS (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The article analyzes the beginning of the 1916 uprising in southern Kyrgyzstan and the actions of the leaders of this uprising. Using historical sources, the main prerequisites, causes and reasons for the 1916 uprising in this region are studied. The colonial policy of tsarism led to the impoverishment of the local population, the main wealth - the land ended up in the hands of the colonial power, the number of settlers increased every year and they were given the best lands of local indigenous residents. Among the reasons for the uprising is the deterioration of the social situation of the population, especially during the First World War. The reason for the uprising of 1916 in the south of Kyrgyzstan was the tsar’s Decree of June 25, 1916 on the mobilization of indigenous people of Central Asia for rear work. The local population opposed mobilization and thus refused to go to rear work. The uprising began in Khujand, and was also picked up in other districts of southern Kyrgyzstan. Uprisings took place in all districts and in ayils, as well as in the cities of the Fergana Valley. The main driving forces of the 1916 uprising were the common people, led by strong, brave and selfless horsemen. But the tsarist government, using punitive detachments, dealt cruelly with the rebels.
Keywords: uprisings, prerequisites, reasons, cause, war, settlers, leaders